Chronic obstructive pulmonary disease (COPD) and COPD-like phenotypes - Spyridon Fortis; Spyridon Fortis; Spyridon Fortis; Dimitris Georgopoulos; Nikolaos Tzanakis; Frank Sciurba; Joseph Zabner; Alejandro P. Comellas (Frontiers in Medicine, 2024)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease. Historically, two COPD phenotypes have been described: chronic bronchitis and emphysema. Although these phenotypes may provide additional characterization of the pathophysiology of the disease, they are not extensive enough to reflect the heterogeneity of COPD and do not provide granular categorization that indicates specific treatment, perhaps with the exception of adding inhaled glucocorticoids (ICS) in patients with chronic bronchitis. In this review, we describe COPD phenotypes that provide prognostication and/or indicate specific treatment. We also describe COPD-like phenotypes that do not necessarily meet the current diagnostic criteria for COPD but provide additional prognostication and may be the targets for future clinical trials.